Method for testing and evaluating non-magnetic stainless steel for instrument while drilling in logging industry
Through comprehensive testing and evaluation of magnetic-free stainless steel materials, we can screen and meet the high requirements of drilling instruments in the well logging industry, solve the problem of corrosion and cracking of materials in the existing technology under complex working conditions, and improve the reliability of drilling instruments.
Patent Information
- Application Number
- CN202411726816.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
It is difficult to effectively screen out the existing technology to meet the high requirements of magnetic-free stainless steel materials for drilling instruments in the well logging industry, especially in complex downhole conditions, the materials are prone to corrosion and cracking.
A test and evaluation method for non-magnetic stainless steel for drilling instruments in well logging industry is proposed, including testing of chemical composition, mechanical properties, magnetic properties, corrosion resistance, welding properties, internal defects, purity, grain size, etc. on a variety of non-magnetic stainless steel materials, and determining materials that meet the usage requirements based on the usage conditions, setting thresholds to judge the applicability of other materials.
Through this test and evaluation method, non-magnetic stainless steel materials that meet complex underground working conditions can be effectively screened out, which improves the working reliability of drilling instruments and avoids corrosion and cracking problems.
Smart Images

Figure BDA0005159400930000031 
Figure BDA0005159400930000071 
Figure BDA0005159400930000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of stainless steel performance testing, and in particular relates to a testing and evaluation method for non-magnetic stainless steel used in drilling instruments in the well logging industry. Background Art
[0002] In the field of logging while drilling, non-magnetic stainless steel materials are widely used in key components such as non-magnetic drill collars. However, the use environment of non-magnetic stainless steel materials for logging while drilling instruments is very harsh. The main reasons are as follows: the drilling depth is getting deeper and deeper, and the strata being traversed are becoming more and more complex; the temperature in the drilling area reaches or exceeds 200°C; the mud contains chlorides, acids, alkalis and other substances; during the drilling process, non-magnetic stainless steel materials are subjected to stress such as extrusion, bending, torsion, high-frequency vibration, and high pressure. In these environments, non-magnetic stainless steel materials for logging while drilling instruments will suffer from corrosion and cracking problems.
[0003] Therefore, the complex working conditions underground require non-magnetic stainless steel materials to meet higher requirements in terms of mechanical properties, corrosion resistance, etc. However, the current research on non-magnetic stainless steel for drilling instruments only focuses on technical research such as material preparation, process control, microstructure, and a certain corrosion test of non-magnetic stainless steel.
[0004] Based on this, this field urgently needs to develop a testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry, so as to screen out non-magnetic stainless steel materials that meet the requirements of non-magnetic stainless steel for drilling instruments in the well logging industry. Summary of the invention
[0005] The purpose of the present invention is to provide a test and evaluation method for non-magnetic stainless steel used for drilling instruments in the well logging industry in view of the defects of the prior art.
[0006] Specifically, the testing and evaluation method of non-magnetic stainless steel for drilling instruments in the well logging industry of the present invention is implemented by the following technical solutions:
[0007] A test and evaluation method for non-magnetic stainless steel used in drilling instruments in the well logging industry, comprising:
[0008] (1) Test a variety of non-magnetic stainless steel materials and record the test results;
[0009] The test contents include: chemical composition, mechanical properties, magnetic properties, corrosion resistance, weldability, internal defects, purity, and grain size;
[0010] (2) applying the non-magnetic stainless steel material to drilling instruments in the well logging industry, and determining the non-magnetic stainless steel material that meets the use requirements according to the use conditions;
[0011] (3) Sorting out the test results of non-magnetic stainless steel materials that meet the use requirements and determining the threshold value of each test result;
[0012] (4) Using the threshold as a standard, it is judged whether other types of non-magnetic stainless steel materials meet the use requirements of drilling instruments in the well logging industry.
[0013] The above-mentioned testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry, the chemical composition of the non-magnetic stainless steel material that meets the use requirements should meet the following requirements: chromium 18wt% ~ 20wt%, manganese 20wt% ~ 21.5wt%, nitrogen 0.50wt% ~ 0.80wt%, molybdenum 1.5wt% ~ 2.5wt%, nickel 3wt% ~ 4.5wt%.
[0014] The above-mentioned testing and evaluation method for non-magnetic stainless steel for drilling instruments in the logging industry, the mechanical properties of the non-magnetic stainless steel material that meets the use requirements are: tensile strength ≥1035Mpa; yield strength ≥965Mpa when the outer diameter is ≤254mm, and when the outer diameter is >254mm, the yield strength ≥896Mpa; elongation after fracture ≥20%; cross-sectional shrinkage ≥50%; impact energy ≥82J; hardness HRC37.5~HRC45.4 or HBN350~HBN430; fatigue performance tension, compression or bending ±448Mpa ≥10 million times, ±552Mpa ≥100,000 times.
[0015] In the above-mentioned testing and evaluation method for non-magnetic stainless steel used in drilling instruments in the well logging industry, the magnetic properties of the non-magnetic stainless steel material that meets the use requirements are: relative magnetic permeability ≤1.005, magnetic field gradient ≤50gammas.
[0016] The above-mentioned testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry, the corrosion resistance of the non-magnetic stainless steel material that meets the use requirements is: according to ASTM A 262 method A, the oxalic acid corrosion test is carried out, the metallographic characteristics of the sample are observed under a microscope, and the etched structure is a step structure or a double structure; according to the ASTM G 36 method, the fracture time of the sample in the specified corrosion and stress environment should be greater than 1000 hours; according to the ASTM G 150 method, the critical pitting temperature of the material should be ≥30°C.
[0017] The above-mentioned testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry, the weldability of the non-magnetic stainless steel material that meets the use requirements is: tested according to ASTM A 262 method E, and no cracks shall appear after the plate specimen is bent at least 90°.
[0018] In the above-mentioned testing and evaluation method for non-magnetic stainless steel used in drilling instruments in the well logging industry, the internal defects of the non-magnetic stainless steel material that meets the use requirements are: ultrasonic flaw detection is performed in accordance with ASTM A 745, and the quality grade should be QL2 and above.
[0019] In the above-mentioned test and evaluation method for non-magnetic stainless steel used in drilling instruments in the well logging industry, the purity of the non-magnetic stainless steel material that meets the use requirements is:
[0020]
[0021] Among them, each type of inclusion has a content level ranging from 0.5 to 3, with a step difference of 0.5, a total of 6 levels, and the grading is in accordance with ASTM E-45.
[0022] In the above-mentioned testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry, the grain size of the non-magnetic stainless steel material that meets the use requirements is: the grain size is tested in accordance with ASTM E 112, and the maximum difference in the average grain size grade at different positions on the same cross section of the rod should not be greater than 3.
[0023] The technical solution of the present invention has the following beneficial effects:
[0024] The present invention proposes a testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry, including testing methods and specific requirements for chemical composition, microstructure, mechanical properties, corrosion resistance, welding sensitivity, magnetism, etc. Through the testing and evaluation method of the present invention, non-magnetic stainless steel that meets the actual downhole drilling conditions can be screened out to ensure the working reliability of the drilling instruments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the following detailed description of the preferred embodiment.The drawings are only for the purpose of illustrating the preferred embodiments and are not to be construed as limiting the invention.
[0026] Figure 1 It is a schematic diagram showing that the etched tissue is a step structure;
[0027] Figure 2 It is a schematic diagram of the double structure of the etched tissue;
[0028] Figure 3 The metallographic microstructure of D1 material at different positions from the core to the surface;
[0029] Figure 4 This is the metallographic diagram of inclusions at different positions of D1 material;
[0030] Figure 5 The hardness distribution of D1 material at different positions from the core to the surface;
[0031] Fig. 6A It is the fatigue fracture at 1 / 2 radius of D1 material;
[0032] Figure 6B This is the enlarged image of the fatigue source at 1 / 2 radius of D1 material;
[0033] Figure 6C The fatigue source and inclusions at 1 / 2 radius of D1 material;
[0034] Fig.6D The energy spectrum of inclusions at 1 / 2 radius of D1 material;
[0035] Figure 7 The intergranular corrosion morphology of D1 material at different locations;
[0036] Figure 8 The arc top after bending of welding sensitivity specimens at different positions of D1 material;
[0037] Fig. 9 is the critical pitting temperature (CPT) of D1 material at different locations;
[0038] Fig.10 The pitting morphology of D1 material after pitting test at different positions;
[0039] Fig.11 Actual picture of the non-magnetic drill collar for D1 material after 760 hours of work;
[0040] Fig.12 The metallographic microstructure pictures of W1 material at different positions from the core to the surface;
[0041] Fig.13 Metallographic images of inclusions at different positions from the core to the surface of W1 material;
[0042] Fig.14 The hardness distribution of W1 material at different positions from the core to the surface;
[0043] Fig.15A This is the fatigue fracture diagram of W1 material;
[0044] Fig. 15B This is the SEM image of the fatigue fracture of the W1 material;
[0045] Fig.16 The intergranular corrosion morphology of W1 material at different locations;
[0046] Fig.17 The arc top after bending of welding sensitivity specimens at different positions of W1 material;
[0047] Fig.18 is the critical pitting temperature (CPT) of W1 material at different locations;
[0048] Fig.19 The photos of the constant load stress corrosion results of W1 material at different positions;
[0049] Fig. 20The slow tensile stress-strain curves of W1 material at different positions;
[0050] Fig.21 The slow tensile stress corrosion fracture morphology at the 1 / 2 radius position of the W1 material: (a) is the overall fracture morphology; (b) is the enlarged view of the overall fracture morphology; (c) is the center of the fracture; (d) is the edge of the fracture;
[0051] Fig. 22 The slow tensile stress corrosion fracture morphology of the W1 material surface: (a) is the overall fracture morphology; (b) is the enlarged view of the overall fracture morphology; (c) is the center of the fracture; (d) is the edge of the fracture;
[0052] Fig.23 This is a photo of the fracture at the male button of a non-magnetic drill collar made of W1 material after working for 320 hours. DETAILED DESCRIPTION
[0053] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.
[0054] In order to screen out non-magnetic stainless steel that meets actual downhole drilling conditions and ensure the working reliability of drilling instruments, the inventor of this application has provided a relatively comprehensive test and evaluation method for non-magnetic stainless steel for drilling instruments in the logging industry through many years of engineering application and a large number of experimental tests.
[0055] Specifically, the testing and evaluation method of non-magnetic stainless steel for drilling instruments in the well logging industry of the present invention comprises:
[0056] (1) Test a variety of non-magnetic stainless steel materials and record the test results;
[0057] The test contents include: chemical composition, mechanical properties, magnetic properties, corrosion resistance, weldability, internal defects, purity, grain size and fatigue test;
[0058] (2) applying the non-magnetic stainless steel material to drilling instruments in the well logging industry, and determining the non-magnetic stainless steel material that meets the use requirements according to the use conditions;
[0059] (3) sorting out the test results of the non-magnetic stainless steel material that meets the use requirements and determining the threshold value of each test result;
[0060] (4) Using the threshold as a standard, it is judged whether other types of non-magnetic stainless steel materials meet the use requirements of drilling instruments in the well logging industry.
[0061] The testing and evaluation method of non-magnetic stainless steel for drilling instruments in the well logging industry of the present invention can provide a comprehensive testing and evaluation of non-magnetic stainless steel for drilling instruments. In practice, the non-magnetic stainless steel screened by the method of the present invention has no problems after multiple actual engineering applications (such as key components such as non-magnetic drill collars), which effectively ensures the working reliability of the drilling instruments.
[0062] The plurality of non-magnetic stainless steel materials in step (1) include a plurality of imported non-magnetic stainless steels and domestic non-magnetic stainless steel materials.
[0063] The following is a detailed introduction to the contents of various tests on non-magnetic stainless steel materials:
[0064] Chemical composition analysis test
[0065] Among them, a carbon-sulfur analyzer is used to test the C and S components of the non-magnetic stainless steel material, an oxygen-nitrogen-hydrogen analyzer is used to analyze the N of the non-magnetic stainless steel material, and an ICP spectrometer is used to test other elements of the non-magnetic stainless steel material.
[0066] Among them, the test of the content of each element can be carried out using existing testing methods, optionally, such as: the Mn content is tested according to the method recorded in NACIS / CH 026:2013, the C content is tested according to the method recorded in GB / T20123-2006, the Cr content is tested according to the method recorded in GB / T 223.11-2008, the Mo and Ni contents are tested according to the method recorded in NACIS / CH 008:2020, and the N content is tested according to the method recorded in GB / T 20124-2006.
[0067] After a large number of imported non-magnetic stainless steels, domestic non-magnetic stainless steel materials and many years of engineering applications, the chemical composition of non-magnetic stainless steel materials that meet the use requirements should meet the following requirements: chromium 18wt% ~ 20wt%, manganese 20wt% ~ 21.5wt%, nitrogen 0.50wt% ~ 0.80wt%, molybdenum 1.5wt% ~ 2.5wt%, nickel 3wt% ~ 4.5wt%.
[0068] Mechanical properties test
[0069] Wherein, the mechanical property test includes tensile, impact, hardness and fatigue tests on the material.
[0070] Optionally, the tensile test is carried out according to the method described in GB / T228.1-2020. Wherein, the tensile rate is: 3X10 - 3cm / s (2mm / min); sample size: D=5mm, parallel section Lc=35mm, gauge length: 25mm; sampling: surface (2CM below the surface), 1 / 4 radius, 3 / 4 radius, center, or surface (2CM below the surface), 1 / 3 radius, 2 / 3 radius, center.
[0071] Optionally, the impact test is performed according to the method described in GB / T 19748-2005, wherein the V-notch direction is: the front side faces the longitudinal opening; the notch angle is 45°; the notch depth (mm): 2; the test temperature is room temperature; and the sample size is 10x10x55 (mm).
[0072] Optionally, hardness mechanics is performed according to the method described in GB / T 4340.1-2009, wherein the indenter continuously punches points, and the indenter of 10 kg continuously punches points from 1 cm below the surface to the center, and punches points in two vertical quadrants.
[0073] Optionally, the fatigue performance test of non-magnetic stainless steel materials can be carried out according to the method described in GB / T 3075-2021. Among them, the frequency is 100Hz; the maximum stress is 550Mpa; the wave type is sinusoidal; the stress ratio is -1; the cycle is 10 5 Weekly test sample: parallel length L: 30mm; d: 6mm.
[0074] After a large number of imported non-magnetic stainless steels, domestic non-magnetic stainless steel materials and many years of engineering applications, the mechanical properties of non-magnetic stainless steel materials that meet the requirements are shown in Table 1
[0075] Table 1 Mechanical properties requirements
[0076]
[0077] Magnetic test
[0078] The magnetic test of non-magnetic stainless steel material can be carried out according to the method described in ASTM-A 342 Method 1.
[0079] After testing a large number of imported non-magnetic stainless steels, domestic non-magnetic stainless steel materials and many years of engineering applications, the magnetic properties of non-magnetic stainless steel materials that meet the use requirements are: relative magnetic permeability ≤1.005, magnetic field gradient ≤50gammas.
[0080] Corrosion resistance test
[0081] Among them, the corrosion resistance test of non-magnetic stainless steel materials includes: intergranular corrosion, pitting corrosion and stress corrosion tests on the forging surface, 1 / 4 radius, 3 / 4 radius and center.
[0082] Alternatively, intergranular corrosion performance testing may be performed using the method described in ASTM A262 Method "A".
[0083] Optionally, the pitting corrosion performance test can be performed using the method described in ASTM G150, wherein the solution is a saturated NaCl solution (6 mol / L); the polarization constant potential is -100 mV (SCE).
[0084] Optionally, the stress corrosion performance test can be performed using the method described in ASTM G123-2000 (2015), wherein the medium is 25% NaCl, pH is 1.50, temperature is boiling 106°C to 110°C, stress is 45 ksi, and the rod section of the 1000h tensile sample has a diameter of 3.81 mm and a length of 76.2 mm.
[0085] After a large number of imported non-magnetic stainless steels, domestic non-magnetic stainless steel materials and many years of engineering applications, the corrosion resistance of non-magnetic stainless steel materials that meet the use requirements is: according to ASTM A 262 method A, the oxalic acid corrosion test is carried out, and the metallographic characteristics of the sample are observed under a microscope. The etched structure is a step structure (see Figure 1 ) or dual structure (see Figure 2 ); When tested according to ASTM G123-2000 (2015), the fracture time of the specimen in the specified corrosion and stress environment should be greater than 1000 hours; when tested according to ASTM G 150, the critical pitting temperature of the material should be ≥30°C.
[0086] Weldability test
[0087] Alternatively, the weldability of non-magnetic stainless steel materials may be tested in accordance with ASTM A 262 Method E.
[0088] After testing a large number of imported non-magnetic stainless steels, domestic non-magnetic stainless steel materials and many years of engineering applications, the weldability of non-magnetic stainless steel materials that meet the use requirements is: when tested according to ASTM A 262 Method E, no cracks shall appear after the plate specimen is bent at least 90°.
[0089] Internal defect testing
[0090] Alternatively, non-magnetic stainless steel materials may be ultrasonically tested according to the method described in ASTM A 745.
[0091] After testing a large number of imported non-magnetic stainless steels, domestic non-magnetic stainless steel materials and many years of engineering applications, the internal defects of non-magnetic stainless steel materials that meet the use requirements are: the quality grade should be QL2 and above.
[0092] Purity test
[0093] Optionally, the purity of the non-magnetic stainless steel material may be tested according to the method described in ASTM E45.
[0094] After testing a large number of imported non-magnetic stainless steels, domestic non-magnetic stainless steel materials and many years of engineering applications, the purity of non-magnetic stainless steel materials that meet the use requirements is shown in Table 2.
[0095] Table 2 Purity of non-magnetic stainless steel materials that meet the use requirements
[0096]
[0097] Note 1: Category A is sulfide, Category B is alumina, Category C is silicate, and Category D is spherical oxide; Note 2: Each category of inclusions is graded from 0.5 to 3 with increasing content, with a grade difference of 0.5, for a total of 6 grades, and the grading is in accordance with ASTM E-45.
[0098] Grain size test
[0099] Alternatively, the grain size of the non-magnetic stainless steel material may be tested according to the method described in ASTM E 112.
[0100] After testing a large number of imported non-magnetic stainless steels, domestic non-magnetic stainless steel materials and many years of engineering applications, the grain size of the non-magnetic stainless steel material that meets the use requirements is: the maximum difference in the average grain size grade at different positions on the same cross section of the rod should not be greater than 3.
[0101] Example
[0102] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods without specific conditions in the following examples are based on conventional methods and conditions.
[0103] Example 1
[0104] The test material is a non-magnetic stainless steel product D1 from a domestic manufacturer. The product specification is a forged rod with a diameter of 190 mm and a length of 7.5 inches.
[0105] 1. Chemical composition detection
[0106] The chemical composition of D1 material was tested according to the methods described in NACIS / CH 026:2013, GB / T 20123-2006, GB / T 223.11-2008, NACIS / C H008:2020, and GB / T 20124-2006.
[0107] Table 3 shows the main chemical composition of D1 material, and Table 4 shows the standard chemical composition of the evaluation method proposed by the present invention. It can be seen from Tables 3 and 4 that D1 material basically meets the chemical composition standard of the evaluation method proposed by the present invention. The main elements in non-magnetic stainless steel material are Ni, Mn, N, Cr and Mo, which play a role in strengthening and improving corrosion resistance. Among them, the strengthening elements are mainly N and Mn, and the elements that improve corrosion resistance are mainly N, Cr, Ni, and Mo. At the same time, it is also necessary to ensure that the organization of the material is a full austenite organization, so the addition of N, Mn, and Ni helps to expand the austenite zone and form an austenite organization.
[0108] Table 3 Main chemical composition of materials (mass fraction, %)
[0109] C P Si Ni N Mn S Cr Mo 0.059 0.016 1.21 3.27 0.56 20.2 0.0051 19.34 2.03
[0110] Table 4 Standard chemical composition of the evaluation method proposed in the present invention (mass fraction, %)
[0111] Element Ni N Mn Cr Mo standard 3-4.5 0.5-0.8 20-21.5 18-20 1.5-2.5
[0112] 2. Microstructure Analysis
[0113] 2.1 Metallographic structure
[0114] The grain size of D1 was measured according to the method described in ASTM E 112. Figure 3 The metallographic structure of D1 material from the core to the surface at different positions. It can be seen from the figure that the structure of the material is austenite equiaxed crystal, with some annealing twins, no precipitation at the grain boundary, and no mixed crystal. From Table 6, it can be seen that the grain size of the material is fine on the surface and coarse in the core, and the grains gradually become coarser from the surface to the core. Combined with the grain size rating of the material in Table 5, it can be seen that the grain size of D1 material is 5-7.5.
[0115] Table 5 Grain size rating of materials at different locations
[0116] Heart 1 / 3 of the radius 2 / 3 of the radius surface Level 5 6.5 6.5 7.5
[0117] Table 6 Grain size of materials at different positions from the core to the surface (μm)
[0118] Heart 1 / 3 of the radius 2 / 3 of the radius surface 53.86 52.50 31.54 15
[0119] 2.2 Purity Analysis
[0120] The purity of D1 material was tested according to the method described in ASTM E45.
[0121] Table 7 shows the inclusion ratings at different locations of the material, and Table 8 shows the size distribution of inclusions at 1 / 2 radius of the material. Figure 4The metallographic diagram of inclusions at different positions of the material. As can be seen from the figure, inclusions are distributed in all positions of the material, mainly in two categories: type B alumina and type D spherical oxide. D1 is mainly composed of type B and type D, and the largest inclusion is level 1.
[0122] Table 7 Rating of inclusions in different positions of materials
[0123]
[0124] Table 8 Inclusion size distribution at 1 / 2 radius of the material (μm)
[0125]
[0126] 3. Mechanical properties testing
[0127] 3.1 Tensile properties
[0128] The tensile properties of D1 material were tested according to the method described in GB / T228.1-2020. The tensile rate is 3X10 -3 cm / s (2mm / min); sample size: D=5mm, parallel section Lc=35mm, gauge length: 25mm; sampling: surface (2CM below the surface), 1 / 4 radius, 3 / 4 radius, center.
[0129] Table 9 shows the tensile performance data of D1 material at different positions, and it can be seen that: elongation %: 28.5-43. The tensile strength and yield strength of D1 material both show a trend of gradually decreasing from the surface to the core; due to the large surface stress value and poor plasticity, the elongation of the material surface is lower than that of the core.
[0130] Table 10 is the standard mechanical property requirements of the evaluation method proposed by the present invention. It can be seen from the table that the tensile strength and yield strength of the D1 material core fail to meet the evaluation method standards proposed by the present invention, but the material in the center of the non-magnetic drill collar must be removed by processing, and the rest of the positions basically meet the standards, and the elongation meets the standards, so the mechanical properties of the D1 material meet the standards proposed by the present invention. (Note: The surface refers to 2CM below the surface)
[0131] Table 9 Tensile properties of D1 material at different positions from the core to the surface
[0132]
[0133] Table 10 Mechanical properties requirements of the evaluation method proposed in this invention
[0134]
[0135] 3.2 Impact performance
[0136] The impact performance test of D1 material was carried out according to the method described in GB / T 19748-2005. The V-notch direction: the front side faces the longitudinal opening; the notch angle: 45°; the notch depth: 2mm; the test temperature: room temperature; the sample size: 10x10x55 (mm).
[0137] Table 11 shows the impact performance data of the material at different positions. The impact toughness of the D1 material meets the evaluation method standard proposed in the present invention.
[0138] Table 11 Impact properties of materials at different positions from the core to the surface (J)
[0139]
[0140] 3.3 Hardness
[0141] The hardness of D1 material was tested according to the method described in GB / T 4340.1-2009. The indenter continuously punched points, with a 10 kg indenter punching points from 1 cm below the surface to the center, in two vertical quadrants.
[0142] Figure 5 This is the distribution of Brinell hardness at different locations of the material. The indenter diameter used is 2.5mm and the load is 187.5Kg. Figure 5 It can be seen that the hardness distribution of the materials shows a trend of gradually decreasing from the surface to the core, and the hardness values of the surface and the core are quite different. The hardness values of the surface and the core of the D1 material differ by about 105HB. The hardness value of the core of the D1 material is not within the reference value, and the other positions meet the standard. However, the material in the center of the non-magnetic drill collar needs to be processed and removed, and the other positions basically meet the standard. The present invention does not require the hardness but only provides a reference value. Therefore, the hardness of the D1 material meets the standard proposed by the present invention.
[0143] 3.4 Fatigue performance
[0144] The fatigue performance of non-magnetic stainless steel material D1 was tested according to the method described in GB / T 3075-2021. The frequency was 100Hz; the maximum stress was 550Mpa; the wave type was sinusoidal; the stress ratio was -1; the cycle was 10 5 Weekly test sample: parallel length L: 30mm; d: 6mm.
[0145] Table 12 shows the fatigue properties at 1 / 2 radius and two positions on the surface of the material. Two parallel samples were taken at each position for repeated experiments. Fatigue test parameters: loading waveform is sine wave, maximum stress is 550MPa, stress ratio is -1, and test frequency is 50Hz.
[0146] It can be seen from Table 12 that the fatigue properties of the materials are all better on the surface than at the 1 / 2 radius, and the materials exceed the minimum requirement of 100,000 cycles required by the evaluation method standard proposed in the present invention.
[0147] Fig. 6A It is the fatigue fracture at 1 / 2 radius of D1 material; Figure 6B This is the enlarged image of the fatigue source at 1 / 2 radius of D1 material; Figure 6C The fatigue source and inclusions at 1 / 2 radius of D1 material; Fig.6D is the energy spectrum of inclusions at 1 / 2 radius of D1 material. Figure 6B It was found that the fatigue source of the material fracture did not show an obvious fisheye shape, but the fracture was still a fatigue source, expansion zone and instantaneous fracture zone; many tiny cracks were found at the fatigue source, indicating that the fatigue fracture of the material was in the form of multiple cracks near the surface. In addition, less Al 2 O 3 Inclusions, inclusions are also a major cause of crack sources. The fracture surface and fracture mode of the material are similar.
[0148] Table 12 Fatigue properties of materials at different positions
[0149]
[0150] 4. Corrosion performance testing
[0151] 4.1 Intergranular corrosion
[0152] According to ASTM A262 method A, oxalic acid electrolysis was performed on four locations of the material, namely, the center, 1 / 3 radius, 2 / 3 radius and the surface, to observe the intergranular corrosion resistance of the material. Figure 7 This is the intergranular corrosion metallographic diagram of the material in use after oxalic acid electrolysis. From the diagram, it can be observed that each position of the material has a step-like structure, no corrosion grooves are generated, and the intergranular corrosion resistance is relatively good.
[0153] 4.2 Welding sensitivity
[0154] According to ASTM A262 E method, the welding sensitivity test was conducted on the core, radius 1 / 3, radius 2 / 3 and surface of the material. The sample was first sensitized (677℃ for 30min, water quenched), then boiled in copper-copper sulfate-16% sulfuric acid solution for 15h, and then bent 180° with a 3mm diameter indenter to observe whether there were cracks at the top of the arc. Table 13 shows the results of the welding sensitivity test at different positions of the material. It can be seen that there are no cracks at all positions of the D1 material, and the welding sensitivity is insensitive; there are no cracks at all positions of the D1 material; Figure 8 Macroscopic images of the arc top at different positions of the material.
[0155] Table 1 Welding sensitivity performance of 3D1 material at different positions
[0156]
[0157] 4.3 Critical pitting temperature
[0158] According to ASTM G150, the critical pitting temperature test was conducted on the core, radius 1 / 3, radius 2 / 3 and surface of D1 material. The critical pitting temperature proposed by the present invention is above 30°C. Table 14 and Fig. 9 The critical pitting temperature (CPT) test results at different positions of the material show that all positions of D1 are above 30°C, and the pitting resistance is good. Fig.10 This is the morphology of pitting pits after pitting corrosion experiments at different positions of the material. It can be seen that pitting pits appeared in the material and pitting corrosion occurred.
[0159] Table 14 Critical pitting temperature (CPT) of different positions of materials
[0160] surface 2 / 3 of the radius 1 / 3 of the radius Heart 32 35 37 35
[0161] 4.4 Stress corrosion
[0162] The boiling magnesium chloride solution stress corrosion test was carried out according to ASTM G36 standard, and the stress corrosion results at different positions of the material are shown in Table 15. The stress corrosion constant load results at different positions of the material D1 all meet the evaluation criteria proposed by the present invention.
[0163] Table 15 Stress corrosion results of materials at different locations
[0164]
[0165] 5. Magnetic test
[0166] Magnetic testing was carried out according to ASTM A342 Method 1. Table 16 shows the magnetic properties of the materials. It can be found that the magnetic permeabilities are all lower than 1.005, which meets the standard requirements.
[0167] Table 16 Magnetic properties of materials
[0168] product <![CDATA[Magnetic permeability μ r > D1 1.003
[0169] 6. Test Summary
[0170] The performance of D1 non-magnetic stainless steel products was tested and analyzed. Based on the composition, microstructure test, mechanical property test, corrosion property test, and magnetic property test of the above high-strength non-magnetic stainless steel, the preliminary conclusions are as follows:
[0171] (1) The microstructure of the non-magnetic stainless steel products in use is austenite equiaxed crystals without mixed crystals; the D1 grain size is 15-53.86μm; the corresponding grain rating is that the D1 material grain size is 5-7.5 grade materials all show a trend of coarse core and fine surface; the difference between the core and surface grain sizes of D1 materials is large, and the overall grain size is fine. D1 inclusions are mainly B and D, and the largest inclusions are all grade 1.5.
[0172] (2) In terms of tensile properties, the elongation of the material is higher than 20%, and the area shrinkage is higher than 50%. The tensile strength of the D1 material at all positions is higher than 1034 MPa, the yield strength at the core position is lower than 965 MPa, and the yield strength at other positions is higher than 965 MPa.
[0173] The impact resistance of the materials all reaches over 80J.
[0174] The hardness of the material, the hardness value of D1 material at the core is slightly lower than 310HB, and the lowest hardness value at the core of D1 is 280HB.
[0175] The fatigue performance of the material at different positions reached more than 100,000 cycles, and the material showed a trend of better surface fatigue performance than that at 1 / 2 radius.
[0176] (3) The intergranular corrosion of the material has qualified step-like structures at all locations.
[0177] In the welding sensitivity test: no cracks appeared at any position of the D1 material, and the anti-sensitivity was good.
[0178] The critical pitting temperature of the material is higher than 30℃ at all positions of D1 material, and can reach 40℃ at some positions, indicating good anti-pitting performance.
[0179] In terms of stress corrosion resistance, D1 material shows a strong discrete trend.
[0180] (4) The magnetic permeability of the material is less than 1.005.
[0181] Based on the above performance indicators, the performance of D1 material all meets the standard requirements proposed by the present invention.
[0182] 7 Application Effects
[0183] Six non-magnetic drill collars were processed using D1 material, with a total of 760 hours of work completed. Penetrant testing was performed on the outer surface of the drill collars and the thread buckles, and no abnormalities were found (see Fig.11 ).
[0184] Comparative Example 1
[0185] The test material is a non-magnetic stainless steel product named W1. The product specification is a forged rod with a diameter of 190 mm and a length of 7.5 inches.
[0186] 1. Chemical composition detection
[0187] The chemical composition of W1 material was tested according to the methods described in NACIS / CH 026:2013, GB / T 20123-2006, GB / T 223.11-2008, NACIS / C H008:2020, and GB / T 20124-2006.
[0188] Table 17 shows the main chemical composition of W1 material, and Table 18 shows the standard chemical composition of the evaluation method proposed by the present invention. Combining Table 1 and Table 2, it can be seen that the chemical composition standard of the evaluation method proposed by the present invention is met, wherein the Mo element content is higher than the content specified in the evaluation method standard proposed by the present invention. According to the pitting resistance equivalent value (PRE) calculated based on the composition, W1 is 34.8, and PRE reaches more than 33.
[0189] The main elements in non-magnetic stainless steel materials are Ni, Mn, N, Cr and Mo. These elements play a role in strengthening and improving corrosion resistance. Among them, the strengthening elements are mainly N and Mn, and the elements that improve corrosion resistance are mainly N, Cr, Ni and Mo. At the same time, it is also necessary to ensure that the material structure is fully austenitic. Therefore, the addition of N, Mn and Ni helps to expand the austenite zone and form an austenitic structure.
[0190] Table 17 Main chemical components (mass fraction, %)
[0191] C P Si Ni N Mn S Cr Mo 0.023 0.021 0.17 3.88 0.61 20.64 0.0015 18.05 2.12
[0192] Table 18 Standard chemical composition of the evaluation method proposed by the present invention (mass fraction, %)
[0193] Element Ni N Mn Cr Mo standard 3-4.5 0.5-0.8 20-21.5 18-20 1.5-2.5
[0194] 2 Microstructure analysis
[0195] 2.1 Metallographic structure
[0196] The grain size of W1 was measured according to the method described in ASTM E 112. Fig.12 The metallographic microstructure pictures of non-magnetic stainless steel from the core to the surface at different positions show that the structure is austenite equiaxed crystals, with some annealing twins and no precipitation at the grain boundaries. The W1 material shows an abnormal trend of fine grains in the core and coarse grains on the surface. The fineness of the core is due to the presence of small, incompletely recrystallized grains that have not grown up, while the completely recrystallized grains are actually coarse.
[0197] Table 19 shows the grain size level at different positions from the center to the surface, and Table 20 shows the grain size at different positions from the center to the surface. It can be seen from the table that the grain size level of W1 material is 5.5-6.5. The overall grains of W1 material are relatively coarse, and the grain size level of the material surface is smaller than that of the center, showing an abnormal trend of coarser surface grains. There are mixed crystals in the grain structure of W1 material, and the mixed crystals near the center and 1 / 3 of the radius are more serious, and the structure is uneven; because there are many small grains that are not completely recrystallized near the center and 1 / 3 of the radius, the grain structure near the center and 1 / 3 of the radius is relatively small as a whole; there are also mixed crystals in other parts, but they are milder than those near the center and 1 / 3 of the radius. The reason for the mixed crystals in W1 material is speculated: the forging temperature is insufficient, resulting in the inability of the center to complete the full recrystallization process, resulting in incompletely recrystallized grains.
[0198] Table 19 Grain size rating at different positions from the center to the surface
[0199] Heart 1 / 3 of the radius 2 / 3 of the radius surface 6.5 6.5 Level 5.5 Level 5.5
[0200] Table 20 Grain size at different positions from the center to the surface (μm)
[0201] Heart 1 / 3 of the radius 2 / 3 of the radius surface 32.31 30.52 50.81 51.38
[0202] 2.2 Purity Analysis
[0203] The purity of W1 material was tested according to the method described in ASTM E45.
[0204] Table 21 shows the inclusion ratings of W1 non-magnetic stainless steel materials at different locations from the core to the surface. Fig.13 The metallographic images of inclusions at different positions from the core to the surface. Combining the inclusion rating data and metallographic images, it can be seen that inclusions are distributed in various positions, mainly D-type spherical oxides. The inclusions of W1 material are mainly D-type spherical oxides. The maximum inclusion rating is 0.5.
[0205] Table 21 Inclusion ratings at different locations from the center to the surface
[0206]
[0207] Table 22 shows the results of Aspex automatic particle scanning on the surface and at the radius 1 / 2. This method can visualize and quantitatively characterize the inclusions of the material and more accurately evaluate the type and distribution of inclusions. The main inclusion types of W1 are Al 2 O 3, MnS, Oxysulfide composite, Silicates, and W1 material also has TiN type inclusions. From Table 22, the inclusion density and total area of W1 are roughly at the same inclusion level, which is consistent with the metallographic method. The inclusions of the material are mainly Al 2 O 3 The majority of inclusions are composite inclusions of quartz and oxysulfide. In addition, W1 also has a relatively large proportion of TiN inclusions.
[0208] Table 22 Aspex fully automatic particle scanning results at different positions
[0209]
[0210] Table 23 shows the inclusion size distribution results at the radius 1 / 2. Most inclusions are small in size, with the size concentrated in the range of <10μm.
[0211] Table 23 Inclusion size distribution at radius 1 / 2 (μm)
[0212]
[0213] 3 Mechanical properties test
[0214] 3.1 Tensile properties
[0215] The tensile properties of W1 material were tested according to the method described in GB / T228.1-2020. The tensile rate is 3X10 -3 cm / s (2mm / min); sample size: D=5mm, parallel section Lc=35mm, gauge length: 25mm; sampling: surface (2CM below the surface), 1 / 4 radius, 3 / 4 radius, center.
[0216] Table 24 shows the tensile performance data at different positions from the core to the surface. It can be seen that: as a whole, the tensile performance of W1 material at each position fluctuates less and is more uniform, but its plasticity is lower. This is because the residual stress of W1 material is large, and a larger forging ratio is used, which sacrifices some plasticity and increases strength.
[0217] Table 25 shows the standard mechanical property requirements of the evaluation method proposed by the present invention. It can be seen from Table 24 that the yield strength and tensile strength of W1 material meet the evaluation method standards proposed by the present invention at all positions. The elongation meets the evaluation method standards proposed by the present invention.
[0218] Table 24W1 tensile properties of material from the core to the surface at different locations
[0219]
[0220]
[0221] Table 25 Evaluation method standard mechanical property requirements proposed by the present invention
[0222]
[0223] 3.2 Impact performance
[0224] The impact performance test of W1 material was carried out according to the method described in GB / T 19748-2005. The V-notch direction: the front side faces the longitudinal opening; the notch angle: 45°; the notch depth: 2mm; the test temperature: room temperature; the sample size: 10x10x55 (mm).
[0225] Table 26 shows the impact performance data of W1 material at different positions from the core to the surface. It can be seen that the impact energy value of W1 material is small and the toughness is low. Combined with the evaluation method standard proposed in the present invention, it can be seen that the impact toughness of W1 meets the evaluation method standard proposed in the present invention.
[0226] Table 26 Impact performance at different positions from the core to the surface (J)
[0227]
[0228] 3.3 Hardness
[0229] The hardness of W1 material was tested according to the method described in GB / T 4340.1-2009. The indenter continuously punched points, with a 10 kg indenter punching points from 1 cm below the surface to the center, in two vertical quadrants.
[0230] Fig.14 The distribution of Brinell hardness at different positions from the core to the surface shows that the hardness of W1 material fluctuates at various positions. Generally, the hardness of the surface is higher than that of the core, and the difference is not large. In addition, the overall hardness of W1 is higher than that of the other two materials. Combined with the evaluation method standard proposed by the present invention, it can be seen that the hardness values at different positions are within the range of 301-425 BHN specified in the standard.
[0231] 3.4 Fatigue performance
[0232] The fatigue performance of W1 material was tested according to the method described in GB / T 3075-2021. The frequency was 100Hz; the maximum stress was 550Mpa; the wave type was sinusoidal; the stress ratio was -1; the cycle was 10 5 Weekly test sample: parallel length L: 30mm; d: 6mm.
[0233] Table 27 shows the fatigue performance at 1 / 2 radius and two locations on the surface of the material. Two parallel samples were taken at each location for repeated experiments. Fatigue test parameters: loading waveform is sine wave, maximum stress is 550MPa, stress ratio is -1, and test frequency is 50Hz. It can be seen from Table 27 that the number of cycles needs to meet the minimum requirement of 100,000 cycles, and the two locations of W1 material did not meet the relevant fatigue performance requirements.
[0234] Fig.15A This is the fatigue fracture diagram of W1 material. Fig. 15B This is the SEM image of the fatigue fracture of the W1 material. It can be seen from the image that the fatigue source of the material fracture does not show an obvious fisheye shape, but the fracture is still a fatigue source, an expansion zone, and a transient fracture zone; many tiny cracks are found at the fatigue source, and inclusions are found at the fatigue source. The cracks are not caused by inclusions, but by multiple points of cracks in the near-surface structure.
[0235] Table 27 Fatigue properties at different positions
[0236]
[0237] 4 Corrosion performance
[0238] 4.1 Intergranular corrosion
[0239] According to ASTM A262 method A, oxalic acid electrolysis was performed on four locations of the material, namely, the center, 1 / 3 radius, 2 / 3 radius and the surface, to observe the intergranular corrosion resistance of the material. Fig.16 This is the intergranular corrosion metallographic diagram of the material in use after oxalic acid electrolysis. It can be observed from the figure that each position has a step-like structure, no corrosion grooves are produced, and the intergranular corrosion resistance is relatively good.
[0240] 4.2 Welding sensitivity
[0241] According to ASTM A262 E method, the welding sensitivity test was conducted on the core, radius 1 / 3, radius 2 / 3 and surface of the material. The sample was first sensitized (677℃ for 30min, water quenched), then boiled in copper-copper sulfate-16% sulfuric acid solution for 15h, and then bent 180° with a 3mm diameter indenter to observe whether there was crack at the top of the arc. Table 28 shows the results of welding sensitivity test at different positions. It can be seen that there are cracks at all positions of W1 material, and some positions are directly broken, and the welding sensitivity is relatively sensitive. Fig.17 The macroscopic pictures of the arc top at different positions show that all positions of W1 are cracked, and some positions are completely broken. The local stress of the tissue at each position of the W1 material is large, which is easy to cause intergranular precipitation during the sensitization process. In addition, mixed crystals appear in the W1 material, which is easy to cause stress concentration. Therefore, in the welding sensitivity bending test, cracks are prone to appear at the U-bend arc top of the material.
[0242] Table 28 Welding sensitivity performance of W1 material at different positions
[0243]
[0244] 4.3 Critical pitting temperature
[0245] According to ASTM G150, critical pitting temperature tests were conducted at four locations: the center, radius 1 / 3, radius 2 / 3, and surface of the material. Table 29 and Fig.18 The experimental results of critical pitting temperature (CPT) at different positions show that the CPT value of W1 material is higher than 30°C. The CPT value of W1 material is relatively stable.
[0246] Table 29 Critical pitting temperature (CPT) at different locations
[0247] Heart 1 / 3 of the radius 2 / 3 of the radius surface 31 31.6 34 33.7
[0248] 4.4 Stress corrosion (boiling sodium chloride solution constant load)
[0249] The boiling sodium chloride solution stress corrosion test was carried out according to ASTM G123 standard. The test was loaded with a constant load of 45 ksi and the solution was a 25% boiling sodium chloride solution.
[0250] Table 30 shows the stress corrosion results at different locations in boiling sodium chloride solution. Fig.19 The following is a photo of a stress corrosion sample. The evaluation method standard proposed in the present invention requires that the non-magnetic stainless steel material used for drill collars meet the requirement of 1000 hours in boiling sodium chloride solution. As shown in Table 30, the W1 material has samples that meet the requirement of 1000 hours at all positions, and only the surface sample No. 1 shows volatility, and fracture occurs in only 65 hours. This type of stress corrosion experiment has volatility, but overall, the W1 material shows excellent stress corrosion resistance in sodium chloride solution.
[0251] Table 30 Constant load stress corrosion results at different positions in boiling sodium chloride solution
[0252]
[0253] 4.5 Stress corrosion (slow stretching in boiling magnesium chloride solution)
[0254] According to GB / T15970.7 standard, a slow strain rate tensile stress corrosion test was conducted in a boiling magnesium chloride solution, the tensile rate was 12 μm / min, the solution was a 45% boiling magnesium chloride solution, and the temperature was 155°C. Fig. 20Table 31 is the slow tensile stress-strain curve at different positions, and Table 32 is the slow tensile stress corrosion results at different positions in boiling magnesium chloride solution. As can be seen from Table 31, the parallel samples of this experiment performed relatively stably, and the experimental volatility was not large; the plastic loss rate of the W1 material at the radius 1 / 2 also reached 83.12%, and the surface plastic loss rate was 87.79%.
[0255] Fig.21 This is the slow tensile stress corrosion fracture morphology at the 1 / 2 radius position of the W1 material; Fig. 22 The slow tensile stress corrosion fracture morphology of the W1 material surface. As can be seen from the figure, the fracture of the W1 material at the radius 1 / 2 and the surface position shows a cleavage fracture morphology at the edge, and there is a small amount of dimples in the center of the sample.
[0256] Table 31 Slow tensile stress corrosion results at different positions in boiling magnesium chloride solution
[0257]
[0258] 5. Magnetism
[0259] Magnetic testing was carried out according to ASTM A342 Method 1. Table 32 shows the magnetic properties. It can be found that the magnetic permeability is less than 1.005, which meets the standard requirements.
[0260] Table 32 Magnetic properties
[0261] product <![CDATA[Magnetic permeability μ r > W1 1.003
[0262] 6 Conclusion
[0263] The performance of W1 non-magnetic stainless steel products was tested and analyzed. Based on the above chemical composition, microstructure test, mechanical property test, corrosion property test, and magnetic property test, the preliminary conclusions are as follows:
[0264] (1) The microstructure of W1 non-magnetic stainless steel products is austenite equiaxed crystals; the W1 grain size is 30.52-51.38μm; the corresponding grain rating is 5.5-6.5. The W1 material shows a trend of fine core and coarse surface. The W1 material has mixed crystals, and the core is more serious; the difference between the core and the surface of the W1 material is small, but the overall grain size is coarse.
[0265] W1 is mainly composed of Class D, with the maximum inclusion grade of 0.5, and they are relatively fine inclusions.
[0266] (2) In terms of tensile properties, the elongation is higher than 20%, and the area reduction is higher than 60%. The tensile strength of the W1 material is higher than 1034MPa at all positions, and the yield strength is only slightly lower than 965MPa at the 1 / 3 radius position, and higher than 965MPa at other positions. The impact performance reaches more than 80J, and a single sample is higher than 121J.
[0267] Hardness, the overall hardness value of W1 material is higher than the standard.
[0268] In the fatigue performance, the fatigue performance of the W1 material surface and the radius 1 / 2 position did not reach 100,000 cycles. The fatigue performance of the material is lower than the standard proposed by the present invention.
[0269] (3) The intergranular corrosion of the material has a qualified step-like structure at each position, which is no different from the standard proposed in the present invention.
[0270] In the welding sensitivity test, cracks appeared in all positions of the W1 material, and the anti-sensitivity was poor.
[0271] Critical pitting temperature, the CPT value of W1 material is higher than 20℃, and the radius 1 / 3 and the surface are more than 30℃. The critical pitting temperature of W1 material is good, which is related to their high PRE value. Compared with the standard proposed by the present invention, the CPT performance of each position of the material is more stable, and the material as a whole is higher than the standard proposed by the present invention.
[0272] In the stress corrosion resistance constant load test, only the surface of the W1 material showed fractures before 1000h, while other locations met the requirement of 1000h without fracture, indicating good stress corrosion resistance.
[0273] (4) The magnetic permeability of W1 material is lower than 1.005,
[0274] Based on the above performance indicators, although the W1 material has reached the standards of the present invention in terms of strength, hardness and stress corrosion resistance, its structure has mixed crystals, and the welding sensitivity test is very sensitive, which does not meet the standard requirements; the material has excellent performance in critical pitting temperature and inclusion level, but the overall fatigue performance of the W1 material is lower than the evaluation standard proposed in the present invention.
[0275] 7 Application Effects
[0276] W1 non-magnetic material was processed into non-magnetic drill collar. After a total of 320 hours of drilling time, the male end of the non-magnetic drill collar broke (see Fig.23 ), the material shows mixed crystals and the fatigue performance does not meet the standards of the evaluation method proposed in the present invention.
[0277] The present invention has been disclosed above with preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be understood as limiting the scope of the present invention. It should be noted that all changes and substitutions equivalent to these embodiments should be deemed to be included in the scope of the claims of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined in the claims.
Claims
1. A test and evaluation method for non-magnetic stainless steel used in drilling instruments in the well logging industry, characterized in that: include: (1) Test a variety of non-magnetic stainless steel materials and record the test results; The test contents include: chemical composition, mechanical properties, magnetic properties, corrosion resistance, weldability, internal defects, purity, and grain size; (2) applying the non-magnetic stainless steel material to drilling instruments in the well logging industry, and determining the non-magnetic stainless steel material that meets the use requirements according to the use conditions; (3) Sorting out the test results of non-magnetic stainless steel materials that meet the use requirements and determining the threshold value of each test result; (4) Using the threshold as a standard, it is judged whether other types of non-magnetic stainless steel materials meet the use requirements of drilling instruments in the well logging industry.
2. The testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry according to claim 1, characterized in that: The chemical composition of the non-magnetic stainless steel material that meets the use requirements should meet the following requirements: 18wt% to 20wt% chromium, 20wt% to 21.5wt% manganese, 0.50wt% to 0.80wt% nitrogen, 1.5wt% to 2.5wt% molybdenum, and 3wt% to 4.5wt% nickel.
3. The testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry according to claim 1, characterized in that: The mechanical properties of the non-magnetic stainless steel material that meets the use requirements are: tensile strength ≥1035Mpa; yield strength ≥965Mpa when the outer diameter is ≤254mm, and yield strength ≥896Mpa when the outer diameter is >254mm; elongation after fracture ≥20%; cross-sectional shrinkage ≥50%; impact energy ≥82J; hardness HRC37.5~HRC45.4 or HBN350~HBN430; fatigue performance tension, compression or bending ±448Mpa ≥10 million times, ±552Mpa ≥100,000 times.
4. The testing and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry according to claim 1, characterized in that: The magnetic properties of the non-magnetic stainless steel material that meets the use requirements are: relative magnetic permeability ≤1.005, magnetic field gradient ≤50gammas.
5. The test and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry according to claim 1, characterized in that: The corrosion resistance of the non-magnetic stainless steel material that meets the use requirements is as follows: an oxalic acid corrosion test is carried out according to ASTM A 262 method A, and the metallographic characteristics of the sample are observed under a microscope, and the etched structure is a step structure or a double structure; the test is carried out according to ASTM G36 method, and the fracture time of the sample in the specified corrosion and stress environment should be greater than 1000 hours; the test is carried out according to ASTM G150 method, and the critical pitting temperature of the material should be ≥30°C.
6. The test and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry according to claim 1, characterized in that: The weldability of the non-magnetic stainless steel material that meets the use requirements is: when tested according to ASTM A 262 method E, no cracks should appear after the plate specimen is bent at least 90°.
7. The test and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry according to claim 1, characterized in that: The internal defects of the non-magnetic stainless steel material that meets the use requirements are: ultrasonic flaw detection is carried out in accordance with ASTM A 745, and the quality grade should be QL2 and above.
8. The test and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry according to claim 1, characterized in that: The purity of the non-magnetic stainless steel material that meets the use requirements is: Among them, each type of inclusion has a content level ranging from 0.5 to 3, with a step difference of 0.5, a total of 6 levels, and the grading is in accordance with ASTME-45.
9. The test and evaluation method for non-magnetic stainless steel for drilling instruments in the well logging industry according to claim 1, characterized in that: The grain size of the non-magnetic stainless steel material that meets the use requirements is: the grain size is tested according to ASTM E 112, and the maximum difference in average grain size grade at different positions on the same cross section of the rod should not be greater than 3.